Chinese: A linguistic introduction - Chaofen, Sun (Cambridge University, 2013)
Chinese is spoken by more people than any other language in the world, and has a rich social, cultural and historical background. This is a comprehensive guide to the linguistic structure of Chinese, providing an accessible introduction to each of the key areas. It describes the fundamentals of its writing system, its pronunciation and tonal sound system, its morphology (how words are structured), and its syntax (how sentences are formed)--as well as its historical development, and the diverse ways in which it interacts with other languages. Setting the discussion of all aspects of Chinese firmly within the context of the languages in use, Chinese: A Linguistic Introduction will be of great benefit to learners wishing to extend their knowledge and competence in the language, and their teachers. It will also be a useful starting point for students of linguistics beginning work on the structure of this major world language.